THE EXPLORATION OF THE SELF IN PICTURES. PHOTO-THERAPY - ELENA NEDELCU; ANDRA NEDELCU (Challenges of the Knowledge Society)
We are living in a world surrounded by images; everywhere we go we are overwhelmed by commercials, plasma screens, posters etc. We get lost in these “perfect” pictures, we dream about that perfect body, that perfect sunny holiday and that perfectly happy family. We spend time consuming those pictures, but we don’t spend time to see ourselves as we are, to discover our inner self. But, can we discover ourselves in pictures? I believe so, but only when the pictures are created and not consumed. When pictures are created, creation becomes therapy and the result of the work becomes a means of self discovery and exploration. There are many examples of artists using different media like: sculpture, painting, installation, video that create pictures making use of their own body/face, of their own lives, of their own dreams, hallucinations or obsessions. This is a good way to bring their problems out of the subconscious, to use them in a creative and playful way, to visualize them and to share them with the world. The paper intends to explore the possibilities of self discovery through creating pictures, and in what proportion this activity can become therapy, art or both. The analysis will focus on the possibilities of accepting and comprehending oneself by taking pictures of oneself; on how genuine self-portraits can overcome the individual conflict between who one actually is, what one believes people’s perceptions of oneself are and who one thinks people want one to be in order to be accepted or even successful.